Portfolio Value at Risk: Concept, Implementation and Models Backtesting - Dalli, Ismail (2011)
This dissertation undertakes a comprehensive framework of the new risk management tool known as Value at risk, VaR. It introduces an in-depth study of the latest literature which is utilized in two different aspects. First, it studies the concept of VaR, origin, parameters, and compares it with other market risk measurements. Then, it defines, evaluates and compares the three most used approaches, historical simulation, variance-covariance, and Monte Carlo simulation to compute VaR. Finally, it addresses the concept of Backtesting VaR models for evaluating the accuracy and performance of such models.